Shooting pool at the Student Union, 1945 - Unidentified photographer (Colorado State University. Libraries, 1945)
A group of female CSU students plays pool in the Student Union.
Not digitized by CSUL Digital Services.
Keywords: Student Union; women; recreation; billiards